A Controlled Experiment of Surface Albedo Modification to Reduce Ice Melt. Issue 12 (20th December 2022) - Johnson, D.; Manzara, A.; Field, L. A.; Chamberlin, D. R.; Sholtz, A.
Abstract: Loss of reflectivity in the Arctic and the wider cryosphere is known to increase global temperature rise through an ice‐albedo feedback loop, which has the potential to lead to loss of summertime ice cover in the Arctic Ocean, and to accelerate global warming. Despite the urgency of this situation, there are few options being developed to preserve and restore ice reflectivity. Localized surface albedo modification using reflective materials offers a potential pathway to restore Arctic ice. We conducted a controlled experiment to determine effects of surface albedo modification on ice melt and thermodynamic processes of a pond. We applied a coating of hollow glass microspheres (HGMs) to a test section, while leaving a control section unmodified. Laboratory measurements show that the loading of HGM materials used corresponds to a reflectivity of 30%. We measured ice and snow thickness, albedo, incoming and outgoing shortwave and longwave radiation, and ice, water, and ambient temperatures. A 1‐D thermodynamic model was developed to quantify the effect of albedo modification on the processes of heat transfer, energy absorption and ice melt. The albedo increased from 0.17 on a control section to 0.36 on a test section. During the 2‐week melt period, there was a 29% reduction in net radiative energy into the test section and a 33% reduction of ice melting rate measured by volume. This experiment using quantitative methods elucidates the mechanisms of ice preservation through surface albedo modification and demonstrates its effectiveness. Plain Language Summary: A method to increase ice retention on pond ice has been tested during the Spring melt season. The test has shown the potential to slow ice loss by using a thin layer of a safe, commonly used reflective material. This albedo‐enhancing approach shows potential to help preserve ice in selected regions in the Arctic and elsewhere, potentially slowing world‐wide rates of global warming and reducing climate instabilities. Key Points: A surface coating of hollow glass microspheres (HGMs) on freshwater pond ice increased the average daily albedo from 0.17 to 0.36 The coating of HGMs reduced the rate of ice melt by 33% from 5 March through 19 March Applied early in the season, HGMs can withstand weathering of a northern climate, reemerging after snowmelt to brighten the ice surface